2021
DOI: 10.1108/qae-02-2021-0028
|View full text |Cite
|
Sign up to set email alerts
|

Exploring impacts on students as givers of teaching feedback

Abstract: Purpose Feedback is usually given for the primary benefit of the feedback recipient and often involves the unidirectional delivery of information. The purpose of this paper is to reverse this emphasis and examines the impacts on students of giving feedback to staff as an ongoing dialogue in the delivery of a teaching unit. Design/methodology/approach This novel study uses surveys and focus groups for an in-depth case study of the impact of students giving feedback to staff. It examines different aspects of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It can assist educators understand the learning experiences of students, evaluate student reactions to current learning content and activities, and improve course design and delivery (Marsh, 2007). While there are some concerns that students are over-surveyed, studies have shown that providing regular feedback gives students an increased sense of being supported and valued (Lane & Meth, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It can assist educators understand the learning experiences of students, evaluate student reactions to current learning content and activities, and improve course design and delivery (Marsh, 2007). While there are some concerns that students are over-surveyed, studies have shown that providing regular feedback gives students an increased sense of being supported and valued (Lane & Meth, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Academic institutions have always aimed to collect and take their students' views into account, in an effort to improve their teaching and curriculums [9,10]. Flodé n [11], with thorough research, focuses on student feedback and its positive acceptance from university teachers, emphasizing that both positive and negative student feedback are equally valuable to their teachers.…”
Section: A the Value Of Student Feedback In Teaching Progressmentioning
confidence: 99%